Recent advances in the application of stable isotopes as nutritional tools in aquaculture - Gamboa Delgado, Julián; Peña Rodríguez, Alberto; Martínez Rocha, Luis; Villarreal Cavazos, David Alonso; Nieto López, Martha Guadalupe; Tapia Salazar, Mireya; Ricque Marie, Denis; Cruz Suárez, Lucía Elizabeth; Le Vay, Lewis; Fernández Díaz, Catalina; Cañavate, José Pedro; Ponce, Marian; et al. (Universidad Autónoma de Nuevo León, 2011)
From an ecological point of view, aquaculture systems consist of simple food webs having a limited number of nutritional sources. These characteristics facilitate the application of stable isotope ratios of carbon and nitrogen (δ13C and δ15N) to assess the flow of dietary components. Due to rapid and measurable bioaccumulation of the heavier stable isotopes, such isotopic shifts can be tracked at different times and at each trophic step to provide an indicator of what dietary components are being incorporated into animal tissue and how fast. The present manuscript presents results from recent, controlled nutritional experiments designed to quantify the relative contribution of dietary carbon and nitrogen supplied by different dietary items. Stable isotopes ratios were measured in a range of food sources and experimental animals. In a first experiment, juvenile shrimp Litopenaeus vannamei were reared on co-feeding regimes having different proportions of live biomass of the green macroalgae Ulva clathrata and inert feed in order to identify nutritional contributions to tissue growth using dual stable isotope analysis. In another trial, nitrogen stable isotopes were measured to explore the relative dietary nitrogen contributions from fish meal and pea meal (Pisum sativum) to the growth of white shrimp postlarvae fed low protein diets having different proportions of both ingredients. In a third, multidisciplinary experiment, Senegalese sole (Solea senegalensis) larvae were used as a model to evaluate the effect of different larval feeding regimes on (1) trypsinogen gene expression (ssetryp1), (2) trypsin and chymotrypsin activities and (3) changes in stable isotope composition to estimate the assimilation of dietary carbon from the larval diets.